Economic Impact of Surveillance of Head Trauma Patients with Coagulopathy and Normal Initial Computed Tomography Scan (ECO-NCT) - Tiago Ribeiro da Costa; Rodrigo Batata; Susana Oliveira; Armindo Fernandes; Sérgio Sousa; Filipe Vaz Silva; Vasco Sá Pinto; Márcia Tizziani; Eduardo Cunha; Alfredo Calheiros (Acta Médica Portuguesa)
Introduction: According to the Portuguese clinical guidelines published in 1999, patients with traumatic brain injury and coagulopathies should remain in-hospital for 24 hours for clinical and image surveillance, despite having an admission computed tomography (CT) scan showing no intracranial lesions. Growing evidence suggests this practice is not only void of clinical relevance, but that it can also be potentially harmful for the patient. Nevertheless, up until now there is no published data concerning the economic impact of this clinical practice. Methods: A cost analysis compared retrospective data from patients admitted to our emergency department during 2022 with a hypothetical scenario in which a patient with an admission CT scan without traumatic lesions was discharged. Clinical data was also retrieved concerning the rate of a delayed intracranial bleeding on 24-hour CT scan and mortality at a six-month-period after discharge. Direct costs for the national health service were determined in terms of funding and time invested by medical teams. Results: From a sample of 440 patients, 436 remained in-hospital for a 24-hour clinical and image surveillance, of which only two (0.5%) showed a new intracranial lesion on the second CT-scan. Neither of these two patients required therapeutic measures to control bleeding and were discharged 36 hours after admission. Out of 440 patients, one patient (0.2%) died of cardiac arrest during the 24-hour surveillance period, despite having an initial normal CT scan showing no brain lesions. Our current surveillance practice directly amounted to €163 157.00, whereas the cost of our hypothetical scenario amounted to €29 480.00: a difference of €133 677.00. The application of our surveillance guideline also meant that nine emergency shifts were devoted to this task, compared to 4.6 hypothetical shifts if patients were discharged after an initial CT scan without traumatic intracranial lesions. Conclusion: In spite of apparently not adding any clinical value to our practice, our in-hospital surveillance may represent a significant financial and time-consuming burden, costing five times as much and demanding our medical teams twice as much work when compared to a scenario without clinical surveillance and 24-hour CT scans.